The Criticism of Eurocentric Education in the Context of Culture and Civilization - Mustafa Gündüz (İnsan & Toplum)
For the last two centuries, “the West” has meant far more than a mere geographical area. Europe’s centrality has been emphasized in the production of culture, civilization, technol- ogy and scientific knowledge and has also created a high-level of perception within various activities. Colonialism, capitalism, industrialism, Orientalism and globalization have all played a dominant role in the formation of this perception. The purpose for the existence of almost all societies around the world has been reduced to the European mindset, effort and culture by these means. There is a swift progression through a cultural uniform world with extreme force- ment by Europe. Education is one of the most important devices in this process. Europe started to implement a significant educational program since after the Industrial Revolution in order to maintain its current advantages and work towards improved conditions. Europe shaped its own society in the way it intended mainly through modern education. Correspondingly, non-Western societies have willfully become supporters of Europa. This process continues onto a global scale with all its delicacy, philosophical background, and inclusiveness. In this paper, modern educa- tion, which has been shaped by the European mentality is criticized by using secondary sources.